The repressor Rgt1 and the cAMP-dependent protein kinases control the expression of the SUC2 gene in Saccharomyces cerevisiae - Gancedo, Juana M.; Flores, Carmen-Lisset; Gancedo, Carlos (Biochimica et biophysica acta, 2015)
A low level of glucose is required for maximal transcription of the SUC2 gene in Saccharomyces cerevisiae. Although the repressor Rgt1 binds the SUC2 promoter in gel-shift assays, it has been reported that Rgt1 has only minimal effects on SUC2 expression. Rgt1 acts together with Mth1 to repress the HXT genes encoding glucose transporters, and the release of Rgt1 from some HXT promoters requires cAMP-dependent protein kinase (PKA) activity. The genes RGT1 and MTH1 have been disrupted and the SUC2 promoter modified in several S. cerevisiae backgrounds. Yeast cells were grown in different carbon sources in the presence or absence of 0.1 or 2% glucose, and invertase was assayed in whole cells. Galactose, glycerol or ethanol hindered invertase induction by low glucose, but lactate did not. During growth in lactate, deletion of RGT1 or MTH1 caused a marked increase in invertase levels, and elimination of the Rgt1-binding site in the SUC2 promoter caused also invertase induction. PKA activity decreased invertase levels in cells growing in lactate, and increased them during growth in lactate+0.1% glucose. The low level of expression of SUC2 in the absence of glucose is mainly due to repression by the Rgt1-Mth1 complex. Repression is dependent on PKA activity, but not on any specific Tpk isoenzyme. The results show that previously overlooked regulatory elements, such as Rgt1 and Tpks, participate in the control of SUC2 expression in S.cerevisiae. •SUC2 is repressed by galactose, glycerol or ethanol, but not by lactate•Rgt1 controls the expression of SUC2, both directly and indirectly•PKA up- or down-regulates SUC2 expression depending on the presence of glucose